Effectiveness of Rehabilitation on Functional Changes of the Respiratory System in Persons with Severe and Critical Form of Covid-19 Disease - Eglė Butkienė; Vaida Aleknavičiūtė-Ablonskė (Lithuanian Sports University, 2022)
Background. It has been established that the disease of Covid-19 negatively affects the functions of the respiratory system of individuals. Since the disease appeared relatively recently, there are not many studies examining the functional state of the respiratory system of individuals after Covid-19 infection, but it is known that individuals who have suffered from a severe or critical form of the Covid-19 disease are diagnosed with many different complications. The aim. To assess the effectiveness of rehabilitation for functional changes in the respiratory system of persons suffering from a severe and critical form of the Covid-19 disease. Methods. 20 persons (11 men and nine women) aged 54.95±5.02 years who suffered from a severe or critical form of the Covid-19 disease participated in the study. Testing was done twice, before and after rehabilitation. During the study, the subjects' respiratory system function was evaluated (Stange-Hench sample, respiratory rate, chest excursion, spirometry (VC, FEV, FEV1). Results. After rehabilitation, the parameters of the Stange and Hench functional tests, respiratory rate, chest excursion and Vital Capacity improved. Conclusion. It was established that after 20 days of rehabilitation, the respiratory system function of persons suffering from a severe or critical form of the Covid-19 disease improved. Keywords: Covid-19, Stange and Hench sample, respiratory rate, chest excursion, spirometry.